Assisting significance of lncRNA ASB16-AS1 in the early detection and prognosis prediction of patients with deep venous thrombosis - Menglan Li; Yingying Li; Dawei Zhang; Cheng Cheng; Meiying Yang; Xiuyin Zhang; Xinming Yu; Bo Lu; Min Wang (BMC Cardiovascular Disorders)
Abstract Background Deep venous thrombosis (DVT) is a kind of vascular obstruction, that commonly and widely occurs in lower limbs. Due to the lack of obvious symptoms in the early stage, the rate of misdiagnosis and missed diagnosis is high. This study evaluated the expression and significance of lncRNA ASB16-AS1 (ASB16-AS1) in DVT aiming to identify a novel biomarker for its screening and monitoring. Methods There were 77 DVT patients and 62 healthy individuals included in this study. Plasma ASB16-AS1 level was evaluated using PCR and compared between DVT and healthy groups. The diagnostic and prognostic values of ASB16-AS1 were assessed with ROC and Cox analyses. The correlation of ASB16-AS1 with patients’ conditions, inflammation, and oxidative stress was evaluated by Spearman correlation analysis. Results ASB16-AS1 was significantly upregulated in DVT (P < 0.001), which could discriminate DVT patients from healthy individuals with high sensitivity and specificity (AUC of ROC = 0.858). Increased ASB16-AS1 was associated with the incidence of complications (P = 0.033) and especially for pulmonary embolism in patients (P = 0.029). ASB16-AS1 was negatively correlated with prothrombin time (PT, r = -0.763), antithrombin level (AT, r = -0.711), and international normalized ratio (INR, r = -0.764), and showed positive correlation with fibrinogen (FIB, r = 0.793) and D-dimer (D-D, r = 0.731). Additionally, ASB16-AS1 was positively correlated with pro-inflammation cytokines (rIL−6 = 0.853, rIL−10 = -0.836, rhsCRP = 0.787) and pro-oxidative stress factors (rSOD = -0.751, rMDA = 0.842, r8-isoPGF 2α = 0.840). Conclusion Upregulated ASB16-AS1 was identified as a diagnostic and prognostic biomarker of DVT and was closely associated with inflammation and oxidative stress during DVT.